Tyrosinase inhibition, antioxidant activity and total phenolic content of selected Mimosaceae pericarps ethanolic extracts / Salfarina Ramli and Nijsiri Ruangrungsi - Ramli, Salfarina; Ruangrungsi, Nijsiri (Faculty of Pharmacy, 2021)
The pericarp is the outer layer of a fruit. Often, pericarps are not used and are usually discarded. However, they may have untapped pharmacological potential. This study explored the tyrosinase inhibition, antioxidant activities, and total phenolic content of five pericarp extracts from Mimosacea family, namely Adenanthera pavonina, Archidendron jiringa, Leucaena glauca, Parkia speciosa and Pithecellobium dulce. Ethanolic extract was obtained after continuous extraction of dried pericarp with petroleum ether, dichloromethane and ethanol using Soxhlet apparatus. L-Tyrosine and L-Dopa are the substrates of tyrosinase in the monophenolase and diphenolase reaction, respectively. Both reactions are crucial in melanin production. Thus, tyrosinase inhibitor has broad potential in the fields of cosmetics and medicine. The antioxidant activity was evaluated by reducing power assay and metal chelating assay. Extracts inhibited both diphenolase and monophenolase reactions were analyzed by HPLC-PDA. From the results, at 500 µg/ml A. jiringa and P. speciosa extracts exhibited both monophenolase and diphenolase reactions. HPLC-PDA analysis detected catechin and epicatechin from the extract, respectively. Inhibition activity of A. jiringa and A. pavonina were not significantly different with kojic acid in monophenolase and diphenolase reaction, respectively. It can be implied that the inhibition of monophenolase reaction was attributed by the high total phenolic content, presence of flavanols and high reducing power. However, reducing power appeared irrelevant to the inhibition of diphenolase reaction, due to the lowest activity presented by the A. pavonina extract. This study showed A. jiringa and A. pavonina extracts inhibited tyrosinase enzyme in different reactions during melanin production.